Inscribed Greek Thunderstones as House- and Body-Amulets in Roman Imperial Times - Faraone, Christopher A. 1955- (2014)
The re-use of Neolithic axe-heads (also known as “celts” or “thunderstones”) as amulets in Roman times is nowadays underappreciated. As a result, the ancient date of two small inscribed examples in the British Museum (BM nos. 1* and 504) is now in doubt,a negative assessment that arises from the use of insufficient comparanda. When compared with the growing corpus of magical gems, the media of these two small axe-heads (jadeite or serpentine), their high polish and their shape do indeed seem suspicious and difficult to assess as gems per se, but when viewed alongside other thunderstones, inscribed and uninscribed, found in Roman and later sites, we can see that both of the London stones belong to a clearly defined category of thunderstones reused as amulets.
La réutilisation des haches néolithiques (également appelées « celts » ou « pierres de foudre ») comme des amulettes à l’époque romaine est aujourd’hui sous-estimée. En conséquence, la date ancienne des deux petits exemples inscrits du British Museum (BM nos 1* et 504) est maintenant remise en doute, en raison d’une évaluation négative qui découle de l’utilisation insuffisante de comparanda. En comparaison avec le corpus croissant de pierres magiques, les médias de ces deux petites haches (jadéite ou serpentine), leur poli et leur forme semblent en effet suspects et difficiles à évaluer comme gemmes en soi, mais quand on les compare à d’autres haches néolithiques inscrites et anépigraphes trouvées dans sites romains et plus tard, il s’avère que les deux pierres à Londres appartiennent à une catégorie bien définie de « pierres de foudre » réutilisées comme amulettes.